Identify the effectiveness of a training program based on remote supervision in developing some of the electronic supervision competencies it among the educational supervisors in the kindergarten stage in the city of Makkah - Al-Saigh, Ohood Khaled; Babtain, Hoda Muhammad (Journal of Curriculum and Teaching Methodology, 2024)
The current study aimed to identify the effectiveness of a training program based on remote supervision in developing some of the electronic supervision competencies it among the educational supervisors in the kindergarten stage in the city of Makkah. To achieve that goal, the study followed the descriptive approach, and the experimental approach based on the one-group pretest-posttest quasi-experimental design. The training program was designed, and the study tools which included: a cognitive test consisting of (20) questions; a performance evaluation card consisting of (18) items distributed on the three axes of electronic supervisory competencies (e-learning competencies, distance training competencies, and the competencies of electronic evaluation), the tools were distributed to the study sample consisting of (23) educational supervisors in kindergarten level in Makkah. Based on a number of statistical methods, the study reached the following results: there were numerous statistically significant differences (α <0.05) between the median average performance of the study sample in the pre and post tests of both the cognitive test and performance evaluation card in total, in favor of the post test was due to the use of the training program based on remote supervision. Considering the results, the study recommended the need to continually develop the techniques of implementing the remote supervision model as a model compatible with the constantly changing requirements of the modern age. This could be done by meeting requirements of its application, whether human or material. This also could be done by focusing on enriching the skills of educational supervisors in the field of electronic supervision competencies through offering training courses in the field of remote supervision. Finally, the study recommended the need for continuous training of educational supervisors in whatever trending in the educational field.